Pendidikan Islamic Parenting dalam Hadith Perintah Salat - M. Burhanuddin Ubaidillah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
Hadith prayer orders textually understood at first glance seem to highlight physical violence that is not relevant to modern education. Textual and contextual understanding of Hadith must distinguish between fixed goals and changing means so that new interpretations of Hadith can be found. The purpose of this study is to explain the concept of Islamic Parenting education in the hadith about prayer orders. The method used is a library review by examining the study of the books and the thoughts of the scholars. Based on Islamic Parenting education can be traced the main spirit that the Prophet's education in practice was actually gentle and proved to have a profound influence on the souls of his friends. Islamic Parenting education aims to provide psychoeducation for parents based on character and Islamic positive habits